The Effect Of The Inquiry Learning Model With The Scaffolding Strategy On Students' Mathematical Literacy - Vera Dewi Susanti; YL Sukestriyarno; Iqbal Kharisudin; Arief Agoestanto (Universitas Negeri Semarang, 2022)
One way to improve the quality of learning is by increasing the relevance of the teaching model. The teaching model is said to be relevant if in the process it can deliver students achieve educational goals. Therefore, efforts are needed to be able to convey the subject matter to students with models that are relevant to student needs. One alternative is to use a scaffolding-based inquiry learning model. The purpose of this study was to determine the effect of the use of a scaffolding-based inquiry learning model on the mathematics learning outcomes of the tenth graders of SMA Kyai Ageng Basyariyah. The samples in this study were two classes, namely, class XA and XB which were selected using the cluster random sampling technique. This study uses a Quasi-Experimental Design research design. The form of quasi-experimental design used in this study is the Nonequivalent Control Group Design. The data obtained were analyzed by descriptive statistics. The data collection technique used in this study is a measurement technique. The results showed that the data were analyzed using the t-test at a significant level of 5%, namely the results of >, namely 1,932 > 1,701. Based on the results of the study, it can be concluded that the use of the scaffolding-based inquiry learning model influences the mathematics learning outcomes of the tenth graders of SMA Kyai Ageng Basyariyah.